Viscosity of fluoroindate glasses - Costa, Bill J. (1998)
The viscosity of two fluoroindate glasses was measured as a function of temperature in the range of 310 °C - 362 °C. In such interval, the viscosity values were found to be similar to those reported for fluorozirconate glasses. The log η - 1/T plots had an unexpected behavior: two viscosity regions that seem to obey Arrhenius equation were identified and the activation energy for viscous flow (EA) for the region near Tg is smaller than the value found above the transition range. This behavior is probably due to structural changes occurred around Tg. The low values of the activation energy for viscous flow obtained for the indium fluoride-based glasses studied, suggest a good resistance against the devitrification process, what can make them suitable for fiber preparation.